2015
DOI: 10.18632/oncotarget.5271
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy and safety of Endostar combined with chemoradiotherapy for patients with advanced, locally recurrent nasopharyngeal carcinoma

Abstract: PurposeTo evaluate the short-term efficacy and safety of recombinant human endostatin (Endostar) combined with chemoradiotherapy for the treatment of advanced, locally recurrent nasopharyngeal carcinoma (NPC).Materials and MethodsBetween March 2010 and October 2013, a total of 22 patients with stage rIII-IVb locally recurrent NPC underwent salvage radiotherapy with Endostar in Sun Yat-Sen University Cancer Center. Intensity-modulated radiotherapy (IMRT) was delivered. Platinum-based chemotherapy was used in a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
34
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(35 citation statements)
references
References 25 publications
1
34
0
Order By: Relevance
“…Endostar, a novel modified recombinant human endostatin, has showed strong antiangiogenic effect on various xenograft tumor model and cancer patients, including NPC. [32][33][34] The results of this study demonstrated that Endostar impeded tumor growth without evident tumor regression and that a significant tumor growth inhibition was not observed until day 8, because Endostar was principally cytostatic rather than cytotoxic. It was also shown that Endostar could reduce the tumor vessels, resulting in the decrease of microvessel density, and subsequently lowered the integrin avβ3 expression.…”
Section: Discussionmentioning
confidence: 74%
“…Endostar, a novel modified recombinant human endostatin, has showed strong antiangiogenic effect on various xenograft tumor model and cancer patients, including NPC. [32][33][34] The results of this study demonstrated that Endostar impeded tumor growth without evident tumor regression and that a significant tumor growth inhibition was not observed until day 8, because Endostar was principally cytostatic rather than cytotoxic. It was also shown that Endostar could reduce the tumor vessels, resulting in the decrease of microvessel density, and subsequently lowered the integrin avβ3 expression.…”
Section: Discussionmentioning
confidence: 74%
“…Twenty-two patients with locally advanced recurrent nasopharyngeal carcinoma (rIII-IVb) were enrolled in a study of rh-endostatin combined with radiochemotherapy [38]. Patients received IMRT treatment, platinum-based adjuvant therapy and IV injection of rh-endostatin at 105 mg/m 2 , continuously for 14 days, in a 21-day treatment cycle.…”
Section: Nasopharyngeal Carcinomamentioning
confidence: 99%
“…The fragment also inhibits FGF-2 and VEGF-induced EC proliferation and migration [86,87]. Relying on its anti-angiogenic properties, endostatin displays potent anti-tumoral effects [88,89,90,91]. Remarkably, the treatment with the recombinant fragment induces vessel normalization and, as a consequence an improved chemotherapy efficacy [92].…”
Section: Collagens: a Major Source Of Anti-angiogenic Fragmentsmentioning
confidence: 99%
“…Remarkably, the treatment with the recombinant fragment induces vessel normalization and, as a consequence an improved chemotherapy efficacy [92]. Clinical trials have also been attempted with seesawing results: some deluded the expectations [93,94], whereas others demonstrated a potential benefit [91,95]. It is possible that this may depend on the tumor type and the quality of the vasculature characterizing each tumor.…”
Section: Collagens: a Major Source Of Anti-angiogenic Fragmentsmentioning
confidence: 99%